FA-1 Case Study of Hog Cholera in Flores 2017 and Its Controlling - Paulus Mbolo Maranata (Hemera Zoa, 2018)
Hog Cholera disease or Classical Swine Fever (CSF) or also known as Pork Sampar is one of the viral diseases that attack pigs. The virus that causes Hog Cholera is the genus Pestivirus. Hog Cholera belongs to one of 25 types of strategic infectious animal diseases listed in the Ministry of Agriculture no. 4026 / Kpts / OT / 140/4/2013 on the Stipulation of Strategic Disease Infectious Diseases (Kementan 2013).Hog Cholera disease only attacks pigs and is spread in various countries in the world. This disease attacks all ages of pigs and if not experienced vaccination morbidity and mortality can reach 100% Spread of this disease through direct and indirect contact. Direct contacts between pigs with pigs themselves or between humans in this case workers, visitors or veterinarians who work on these farms with pigs. Indirect contacts can occur through cage equipment, work clothing or transport equipment used such as motorcycles, wagon or truck carrying. The source of the spread of this virus is blood, nasal and mouth fluids, urine, faeces and semen.Diagnosis of Hog Cholera disease based on clinical symptoms, disease epidemiology, pathology change and histopathology and confirmation of laboratory test result in isolation and virus identification, PCR and serology test result of ELISA and FAT.Prevention in the form of strict biosecurity applications concerning the traffic of livestock, humans and equipment is needed in the prevention of this disease. In addition Hog Cholera Vaccination is the most effective way to do for the prevention of this disease, especially in Hog cholera endemic areas. Until now Hog Cholera can not be treated antibiotics just to deal with secondary infections.The first case of Hog Cholera in Indonesia was found in North Sumatra in early 1994 the introduction of the disease was suspected from Peninsular Malaysia. In 1997 Hog Cholera spread to several other areas in Indonesia namely West Sumatra, Riau, Jambi, DKI, Central Java, West Kalimantan, Bali, North Sulawesi, South Sulawesi and East Nusa Tenggara (NTT).In NTT the Hog Cholera case was first found in Tarus Kabupaten Kupang in 1997 (Santia et al. 2008). In 1998 the disease has spread to several islands in NTT including Sumba, Rote, Sabu Island and several districts on the island of Timor. In 2002 the disease attacked the islands of Alor, Pantar and Pura. The year 2005 was first found in Flores ie in Sikka district although without the occurrence of outbreak (Diarmita 2011)